Prevalence and determinants of vitamin D deficiency in the third trimester of pregnancy: a multicentre study in Switzerland. Issue 3 (10th January 2018) - Krieger, Jean-Philippe; Cabaset, Sophie; Canonica, Claudia; Christoffel, Ladina; Richard, Aline; Schröder, Therese; von Wattenwyl, Begoña Lipp; Rohrmann, Sabine; Lötscher, Katharina Quack
Abstract: Vitamin D deficiency during pregnancy is associated with negative health consequences for mothers and their infants. Data on the vitamin D status of pregnant women in Switzerland are scarce. A three-centre study was conducted in the obstetric departments of Zurich, Bellinzona and Samedan (Switzerland) to investigate the prevalence and determinants of vitamin D deficiency (serum 25-hydroxyvitamin D (25(OH)D)<50 nmol/l) in 3rd-trimester pregnant women living in Switzerland ( n 305), and the correlation between 25(OH)D in pregnant women and their offspring at birth ( n 278). Demographic and questionnaire data were used to explore the determinants of vitamin D deficiency. Median concentration of serum 25(OH)D in the third trimester of pregnancy was 46·0 nmol/l (1st–3rd quartiles: 30·5–68·5), representing a 53·4 % prevalence of vitamin D deficiency. 25(OH)D levels in the umbilcal cord blood (median: 50·0 nmol/l; 1st–3rd quartiles: 31·0–76·6) strongly correlated with mothers' serum 25(OH)D (Spearman's correlation ρ =0·79, P <0·001). Multivariable logistic regression analysis showed that significant determinants of vitamin D deficiency in pregnant women were centre of study, country of origin, season of delivery and vitamin D supplement intake. Near-term BMI, skin colour, use of sunscreen and mothers' education, although each not individually significant, collectively improved the ability of the model to explain vitamin D status. Low vitamin D levels were common in this sample of pregnant women and their newborns' cord blood. Vitamin D supplement intake was the most actionable determinant of vitamin D status, suggesting that vitamin D supplementation during pregnancy should receive more attention in clinical practice.